2001
DOI: 10.1164/ajrccm.163.3.2005075
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Severe Pneumonia in the Very Elderly

Abstract: The etiology of severe pneumonia requiring mechanical ventilation in the very elderly has been imprecise because of lack of comprehensive studies and low yield of diagnostic approach. Overall, 104 patients 75 yr of age and older with severe pneumonia were studied prospectively at two university-affiliated hospitals. Microbial investigation included blood culture, serology, pleural fluid, and bronchoalveolar secretions. Streptococcus pneumoniae (14%), gram-negative enteric bacilli (14%), Legionella sp. (9%), He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
226
3
29

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(264 citation statements)
references
References 28 publications
6
226
3
29
Order By: Relevance
“…It strongly suggested that a lower serum albumin level is related with elderly age and lower performance status of patients with NHAP [16], and in other study of NHAP, poor functional status has been also correlated with the presence of MDR pathogens [18]. We did not investigate patients' performance status in this study; however, performance status may be a potential prognosis factor for patients with HCAP.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It strongly suggested that a lower serum albumin level is related with elderly age and lower performance status of patients with NHAP [16], and in other study of NHAP, poor functional status has been also correlated with the presence of MDR pathogens [18]. We did not investigate patients' performance status in this study; however, performance status may be a potential prognosis factor for patients with HCAP.…”
Section: Discussionmentioning
confidence: 76%
“…We did not find significant different mortality between HCAP and CAP in this study (21.4% vs. 10.0%, respectively: p=0.3544, data not shown), however, lower serum albumin was related with mortality in patients with HCAP (P<0.0308, data not shown). Malnutrition may be one of the most important factors that affects prognosis apart from being a risk factor for pneumonia [17][18].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to point out that the crude mortality of S. pneumoniae was equal in the study by MOINE et al [9] and the present study (35%). Some authors have focused on the potential severity of some bacteriological species (Pseudomonas aeruginosa) in nosocomial pneumonia [35,36], or in CAP [6,37] when structural lung diseases are present (bronchiectasis) [38]. In CAP, the pathogens generally implicated in severe cases have failed to demonstrate a role in poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In a study addressing elderly patients with severe CAP, the incidence of influenza was found to be trivial, however, the bias of serology-based detection has to be taken into account [17]. As far as reported, mortality was always very low.…”
Section: Respiratory Infections H Von Baum Et Almentioning
confidence: 96%